The Analysis of the Mediating Role of Customer Satisfaction in Influencing Loyalty at Sulo Rotan (A Study on Product Quality and Price Perception) - 77, Emilia; Syahran, Syahran (The Future of Education Journal, 2025)
The research is motivated by the increasingly intense competition in the rattan product market, both domestically and globally, which requires companies not only to rely on product quality but also to build a competitive price perception and high customer satisfaction. The research method employed is a quantitative approach using path analysis techniques. Data were collected through questionnaires distributed to 100 Sulo Rotan customers. The results indicate that product quality and price perception have a positive and significant effect on customer satisfaction, and that customer satisfaction plays a significant mediating role in the relationship between product quality, price perception, and customer loyalty.